Primary Breast Adenocarcinoma in Ectopic Breast Tissue in the Vulva. (26th August 2013) - McMaster, Jason; Dua, Anahita; Dowdy, Sean C.
Abstract : Introduction . Accessory breast tissue is a rare finding in the general population with an incidence of 1-2%. An even rarer occurrence is accessory breast tissue afflicted with breast carcinoma. We present a brief report discussing diagnosis and management of a patient who presented with primary breast adenocarcinoma in vulval supranumerary tissue. Brief Report . A 60-year-old Caucasian female presented with a lesion in her left vulva that she first identified during adolescence. The lesion began to grow and ulcerate prompting her to receive treatment. Biopsy was inconclusive, and metastatic workup was negative, so her lesion was treated as an isolated breast lump and removed via wide local excision. Conclusion . Primary breast adenocarcinoma of the vulva is exceedingly rare. A paucity of the literature on this topic unfortunately means that strong evidence does not exist detailing the best management of this patient cohort. However, given that histological data confirms these cancers are virtually the same as breast cancers, it logically follows that the best treatment practices for breast cancer may be applied to treat these patients presenting with primary vulva cancers of ectopic breast tissue.